Culture-Based Dakwah and Education Values: A Study of TGH. M. Najamuddin Makmun’s Work - Ahyar, Ahyar; Imtihan, Nurul; Mukhtar, Wan Khairul Aiman bin Wan (Universitas Islam Negeri Mataram, 2024)
Indonesian religious scholars employ diverse methods of Islamic preachings (da’wah), such as utilizing publications, oral traditions, or a combination of the two. This research aims to identify cultural-specific preaching teachings and educational principles of TGH. M. Najmuddin Makmun's writings, a charismatic tuan guru from Central Lombok. The primary emphasis is in his contemplations regarding the incorporation of educational principles, such as tolerance, humanity, perseverance, humility, and compassion, into his sermons. This study employs qualitative descriptive analysis and hermeneutics as research methods. The data is obtained from TGH's writings and interviews with his children and disciples. Data was also collected through direct observation at the Darul Muhajirin Praya Islamic Boarding School located in Central Lombok. The research findings indicate that TGH. M. Najmuddin Makmun’s writings convey messages regarding the preservation of the Prophet’s traditions and Islamic landmarks by reinforcing narratives that emphasize educational ideals transformed the outlook of the Sasak people in Lombok, fostering more religious devotion and cultural awareness. This research provides a valuable contributions to the utilization of culture-based preaching to foster the development of an Islamic society characterized by tolerance and reverence for cultural heritage.